Algal bioethanol production technology: A trend towards sustainable development. (May 2017) - Bibi, Riaz; Ahmad, Zulfiqar; Imran, Muhammad; Hussain, Sabir; Ditta, Allah; Mahmood, Shahid; Khalid, Azeem
Abstract: Fuel security, economics and climate change issues are creating a requirement for alternative renewable fuels. Bioethanol produced by algal biomass is becoming increasingly popular all over the world due to the sustainability of feed stock and environmentally friendly nature. This review paper describes the bioethanol production technology from algae using various cultivation, harvesting, extraction and commercialization techniques and its environmental perspectives. The economic sustainability of algae-derived bioethanol biofuel depends on the cost of production that could be minimized by producing valuable secondary by-products, which is the aim of current algal biofuel research. Future technologies with sufficient potential for maximum extraction capacity and minimal downstream processing using low cost feedstock will address the cost-effectiveness of renewable bioethanol biofuel.